Intervención de los gobiernos autónomos descentralizados en la protección de los ecosistemas a través de incentivos regulados por ordenanzas. - VEGA DÁVILA, CARLOS PATRICIO (2011)
The Constitution of the Republic of the Ecuador inside the primordial duties of the State in their art. 3, literal 7; expressed: To protect the natural and cultural patrimony of the country. Also their articles 12, 13 section second corresponding to the healthy atmosphere and their articles 14 and 15; their quarter section of the natural resources their art. 408, the section fifth that corresponds to the floor in their art. 409; the same ones that speak of environmental principles, production guarantees consummate preservation and recovery of the natural cycles that allow conditions of life with dignity. Also to stimulate projects of afforestation, reforestation and revegetación, the prevention of the environmental damage and the recovery of the degraded natural spaces. Let us also consider their Section second with respect to the public Administration and their Art. 227 (principles of the Public Administration). - The public administration constitutes a service to the collective that is governed by the principles of effectiveness, efficiency, quality, hierarchy, desconcentración, decentralization, coordination, participation, planning, transparency and evaluation. The protection of the ecosystem: it requires of an urgent intervention, for their preservation. Since they impact many factors like the limitless growth in the population, the ecosystems boscosos that are in our county are more and more threatened. With our project of creating a normative one at level of the Decentralized Autonomous Governments, we will fix as objective: To inform and to incentivate the citizens of this regions, so that they protect and conserve this vital natural resource and so that they support the development and the application of effective protection measures. Let us also take into account that the Provincial Governments under the Law of Provincial Régime correspond them inside their Art. 7 and their literal ones: to Guide the provincial aspirations related with the economic development, promoting the exploitation and development of the sources of agricultural, cattle, industrial and mining production, for that which will agree the corresponding plans, framing them inside the General Plan of Development; The Provincial Council will make their planning following the conservation principles, development and sustainable use of the natural resources, and; While in their art. 10 of this same Law are granted the following fundamental guarantees to the Provincial advice. The execution of the ordinances, agreements and resolutions of the entity won't be been able to suspend but in accordance with the dispositions of the Law. The public organisms at local, national and regional level, they are forgotten; and in the local plane, it is necessary to convince the consumers that the load of the forests and of the ecosystem in the region has to decrease, and you must develop a way of trying to this ecosystem that keeps in mind the limitation of the natural resources. The objective consists in that so much the local authorities develop and apply their own politicians, norms and protection measures adapted to the local conditions and constitutional precepts. Clearing is then that the Constitution of the Republic of the Ecuador and their laws tune; they point substantially to the protection of the Ecosystem and the development of the towns, we would lack more than normar with our Decentralized Autonomous Governments; certain aspects based on incentives, to wake up an interest in common for the protection of the Ecosystem, and with all these alternatives of world help and of technology; we will be able to achieve the balance of the human existence with the nature. The Incentive should go channeled to the whole community in general, in base of discharges of tributes or of payments for conservation of the Ecosystem for hectare, opportune training with technology of advanced, and for mainly a financing for the development of these projects. Resources that are guaranteed its return to the arks of the Decentralized Autonomous Governments, since doesn't venture as the agriculture in general that depend of the stations and climatic factors for the development and success of the sembríos, let us don't forget then that when it exists drought or winter in abundance the sembríos and crops throw to lose, and in much of the cases the government has had to condone the credits to the farmers, becoming in that way a paternalistic state. And that to more than that, all the Ecuadorians assume these economic losses. Then with more reason we should look for alternative sure of sembríos, so that the State can invest its resources correctly, and guarantee common and sure well-being. After this explanation we have left clear to where we project our investigation. The Social Constitutional Right and the right of the Good one to Live cannot be applied to fullness in our county, for lack of Ordinances guided to Incentives the Protection and Regeneration of the Ecosystems.